THE POTENTIAL OF Paenibacillus spp. AS PLANT GROWTH PROMOTER IN TROPICAL PEAT ECOSYSTEM - Andri Frediansyah; I Made Sudiana (Widyariset, 2013)
Microbial activity in soil play key important role for maintaining ecosystem health. The objective of this research was to explore the potential of bacteria isolated from Kalampangan, Central Kalimantan tropical peat soil as biofertilizer agent. We found 4 isolates have ability to produce amylase and cellulose and have nirK gene as denitrify ability. Base on the 16S rDNA analyses and morphological observation, those bacteria were identified as Paenibacillus durum, Paenibacillus polymyxa, Paenibacillus macerans, and Paenibacillus azotofixans. P. polymyxa also can produce plant growth hormone (indole acetic acid), P. azotofixans contains ow gene indicating that the strain is able to solubilize calcium as well as alluminium phosphate. All strain excepted P. durum was also contains NifH gene indicating that this strain is able to fix N2. With these characteristics the fourth isolates of bacteria can be used as agents of biological fertilizers for peatland.